2011
DOI: 10.1063/1.3640223
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable enhancement in photocurrent of In0.20Ga0.80N photoanode by using an electrochemical surface treatment

Abstract: Articles you may be interested inSignificantly enhanced performance of an InGaN/GaN nanostructure based photo-electrode for solar power hydrogen generation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Recently, we also found that surface pretreatment had similar effects on the Mo-doped BiVO 4 and InGaN photoanodes. [31,32] Therefore, the removal of surface recombination centers can be a universal strategy to improve the photoelectrochemical performance of a photoelectrode.…”
mentioning
confidence: 99%
“…Recently, we also found that surface pretreatment had similar effects on the Mo-doped BiVO 4 and InGaN photoanodes. [31,32] Therefore, the removal of surface recombination centers can be a universal strategy to improve the photoelectrochemical performance of a photoelectrode.…”
mentioning
confidence: 99%
“…Unfortunately, so far, there are not so many reports on nitride related materials for solar hydrogen production. [2][3][4][5][6][7][8][9] The major challenge is due to low water-splitting efficiency. Very recently, we have demonstrated a significant enhancement in solar hydrogen generation efficiency in hydrochloric acid (HCl) electrolyte (pH ¼ 0.1) using our InGaN/GaN nanorod array structures, fabricated by means of a selforganised nickel nano-mask fabrication technique.…”
mentioning
confidence: 99%
“…The etching removes surface recombination centres and thus decreases the fraction of recombining electron‐hole pairs. This leads to a more efficient separation of the electrons and holes and an increased photocurrent density .…”
Section: Resultsmentioning
confidence: 99%
“…However, the choice of the electrolyte is also very important since the conductivity of pure water is too low for an efficient PEC. In previous reports, a multitude of different electrolytes with different concentrations was used to minimize the resistivity in the cell and to enhance the photoelectrochemical reaction .…”
Section: Introductionmentioning
confidence: 99%